Analisis Perbandingan Metode Fuzzy Mamdani, Sugeno dan Tsukamoto dalam Menghitung Kinerja Dosen - Aulya Kicki Utari; Khafid Nur Ilyas; Muhammad Helmi; Mukti Dwi Atmojo; Wahyu Aji Firmansyah; Perani Rosyani (BISIK : Jurnal Ilmu Komputer, Hukum, Kesehatan dan Sosial Humaniora, 2022)
In college, lecturer performance appraisal is the most influential part in producing the best quality students. Qualified lecturers can also be assessed from the lecturer’s performance. In this fuzzy logic journal comparison, we compare 5 different journals using three different methods, namely Mamdani, Tsukamoto and Sugeno. The purpose of this comparison is to find a good method for assessing lecturers’ performance. With this comparison can produce information that can be used as material to evaluate the performance of lecturers.